Runway Strength Analysis Using ACR-PCR at Sultan Mahmud Badaruddin II Airport - Ria Maya Sari; Melawaty Agustien; Rhaptyalyani Herno Della; Sukahir (Politeknik Penerbangan Indonesia Curug, 2025)
Aircraft Classification Rating-Pavement Classification Rating (ACR-PCR) is a system to determine the PCR value of runway pavement strength and recommended for runway maintenance issued by International Civil Aviation Organization (ICAO) based on ICAO Advisory Circular (AC) 150/5335-5D of 2022, as a replacement for the Aircraft Classification Number - Pavement Classification Number (ACN-PCN) system that has been used since 1980. The implementation of the ACR-PCR Method is determining the strength value of runway pavement can be used as a reference in holding the load of aircraft that have a lower or the same ACR value. The ACR-PCR system was published in order to plan a more rational pavement structure strength by analyzing the response of the pavement structure to the weight of aircraft movement on the runway. The calculation was carried out using the modulus of elasticity of each layer on the runway pavement structure with a more specific type of material. Sultan Mahmud Badaruddin (SMB) II Airport is one of the airports in Indonesia that is currently in the process of transitioning using the ACN-PCN system to ACR-PCR system for runway strength reporting. Base on data of aircraft movement at SMB II airport management in 2024 and calculated by using FAARFIELD 2.1 software, PCR value for the critical runway strength of SMB II Airport was 890 F/C/X/T with a critical aircraft is Boeing B747-400.